Eraluac:ión del comportamiento en semicuutiverio de Tayassu tajacu "Sajino" en el Centro Académico, Investigación y Ecoturismo - Biodiversidad - UNSM - T - Lopez Del Castillo, Magna Consuelo (2004)
Tayassu tajacu "Sajino" is a Peruvian species ofwild fauna, whose scientific data is very limited. Because of this reason, the present investigation work was done apropos of requesting the information about diurna! etiology in semicaptivity of Tayassu tajacu in the Acadernic Center, Investigation and Ecotourism-Biodiversity-UNSM-T., and in sorne way it gives us the information for the future works in investigations related to this important species. Evaluation of the species conduct as in the semicaptivity as in studio and was strictly based on the observation of the direct species conduct; for example: the investigator observes a frill group of the species for individual and registers the specifíc conduct every time. Besides this, the pattems or registration index cards were used as a principal instrument; this method requires only a piece of paper a pen and a great attention from the observer. According to the evaluation of T. tajacu etiology, we have deduced that, on the first hand the category of"Neutral" conduct is presented in major per cent (78.70%), on the second hand we have the "Contact" conduct with 14.35%, consecutive "Vocalization" category (4.35%), "Aggressive" category with 1.76% and finally "Sexual" category with a mínimum per cent of0.83%. T. tajacu is semicaptivity, a species which demonstrates that it has a sociable conduct and helps its reproduction in these conditions; that's why if we help its breeding, we could guarantee its wild survival.